Development And Testing Of Swimming Fish Robot - Low, Jianyan (Universiti Sains Malaysia, 2019)
The “ethorobotics” field is an amazing example of how robotics can provide scientists with unprecedented tools to promote our understanding of laboratory and field animal behavior. The work presented in this thesis is a robotic fish with a wire-driven continuum flapping propulsor and actuated by the biomimetic wire-driven mechanism. The fishtail is made from Expanded Polypropylene. One pair of fishing lines are used to mimic the muscles of the fish and to control the tail flapping. In addition, the tail flapping motion can be controlled to move for propulsion, or for other purposes such as cruising. Next, the experiment was conducted in two stages where the first stage was the fabrication of the entire robot fish which includes the fish body, fishtail and integration of all the electronic devices. Then, the performance of the robotic fish was observed and studied. Thus, the second stage was the analysis of the motion of robotic fish. Therefore, two tests were designed to test the robotic fish in its aquatic environment. The first test aims to assess the ability of robotic fish to swim in a straight horizontal path. From the results, it is important to note that as the flapping amplitude and frequency increased, it was increasingly difficult for the fish robot to swim in a completely straight path and minimal deviation was observed. Next, the second test was used to evaluate the swimming capabilities of the fish robot at variable speeds and thus creating a relationship between the swimming velocity and the flapping amplitude and frequency of fishtail. From the results, the maximum cruising velocity was 0.0716